Human Pupillary Dilation Response to Deviant Auditory Stimuli: Effects of Stimulus Properties and Voluntary Attention - Liao, Hsin-I; Yoneya, Makoto; Kidani, Shunsuke; Kashino, Makio; Furukawa, Shigeto (Frontiers in Neuroscience, 2016)
A unique sound that deviates from a repetitive background sound induces signature neural responses, such as mismatch negativity and novelty P3 response in electro-encephalography studies. Here we show that a deviant auditory stimulus induces a human pupillary dilation response (PDR) that is sensitive to the stimulus properties and irrespective whether attention is directed to the sounds or not. In an auditory oddball sequence, we used white noise and 2000-Hz tones as oddballs against repeated 1000-Hz tones. Participants’ pupillary responses were recorded while they listened to the auditory oddball sequence. In Experiment 1, they were not involved in any task. Results show that pupils dilated to the noise oddballs for approximately 4 s, but no such PDR was found for the 2000-Hz tone oddballs. In Experiments 2, two types of visual oddballs were presented synchronously with the auditory oddballs. Participants discriminated the auditory or visual oddballs while trying to ignore stimuli from the other modality. The purpose of this manipulation was to direct attention to or away from the auditory sequence. In Experiment 3, the visual oddballs and the auditory oddballs were always presented asynchronously to prevent residuals of attention on to-be-ignored oddballs due to the concurrence with the attended oddballs. Results show that pupils dilated to both the noise and 2000-Hz tone oddballs in all conditions. Most importantly, PDRs to noise were larger than those to the 2000-Hz tone oddballs regardless of the attention condition in both experiments. The overall results suggest that the stimulus-dependent factor of the PDR appears to be independent of attention.